“Super” SERPINs—A stabilizing force against fibrinolysis in thromboinflammatory conditions - Humphreys, Steven J.; Whyte, Claire S.; Mutch, Nicola J. (Frontiers in Cardiovascular Medicine, 2023)
The superfamily of serine protease inhibitors (SERPINs) are a class of inhibitors that utilise a dynamic conformational change to trap and inhibit their target enzymes. Their powerful nature lends itself well to regulation of complex physiological enzymatic cascades, such as the haemostatic, inflammatory and complement pathways. The SERPINs α2-antiplasmin, plasminogen-activator inhibitor-1, plasminogen-activator inhibitor-2, protease nexin-1, and C1-inhibitor play crucial inhibitory roles in regulation of the fibrinolytic system and inflammation. Elevated levels of these SERPINs are associated with increased risk of thrombotic complications, obesity, type 2 diabetes, and hypertension. Conversely, deficiencies of these SERPINs have been linked to hyperfibrinolysis with bleeding and angioedema. In recent years SERPINs have been implicated in the modulation of the immune response and various thromboinflammatory conditions, such as sepsis and COVID-19. Here, we highlight the current understanding of the physiological role of SERPINs in haemostasis and inflammatory disease progression, with emphasis on the fibrinolytic pathway, and how this becomes dysregulated during disease. Finally, we consider the role of these SERPINs as potential biomarkers of disease progression and therapeutic targets for thromboinflammatory diseases.